Structure of Fungal α Mating Pheromone in Membrane Mimetics Suggests a Possible Role for Regulation at the Water-Membrane Interface - Partida-Hanon, Angélica; Maestro-López, Moisés; Vitale, Stefania; Turrà, David; Di Pietro, Antonio; Martínez-del-Pozo, Álvaro; Bruix, Marta (Frontiers in Microbiology, 2020)
Fusarium oxysporum is a highly destructive plant pathogen and an emerging pathogen of humans. Like other ascomycete fungi, F. oxysporum secretes α-pheromone, a small peptide that functions both as a chemoattractant and as a quorum-sensing signal. Three of the ten amino acid residues of α-pheromone are tryptophan, an amino acid whose sidechain has high affinity for lipid bilayers, suggesting a possible interaction with biological membranes. Here we tested the effect of different lipid environments on α-pheromone structure and function. Using spectroscopic and calorimetric approaches, we show that this peptide interacts with negatively charged model phospholipid vesicles. Fluorescence emission spectroscopy and nuclear magnetic resonance (NMR) measurements revealed a key role of the positively charged groups and Trp residues. Furthermore, NMR-based calculation of the 3D structure in the presence of micelles, formed by lipid surfactants, suggests that α-pheromone can establish an intramolecular disulfide bond between the two cysteine residues during interaction with membranes, but not in the absence of lipid mimetics. Remarkably, this oxidized version of α-pheromone lacks biological activity as a chemoattractant and quorum-sensing molecule. These results suggest the presence of a previously unidentified redox regulated control of α-pheromone activity at the surface of the plasma membrane that could influence the interaction with its cognate G-protein coupled receptor.